Flora of Espírito Santo: Celastroideae (Celastraceae) - Biral, Leonardo (2023)
Here we present a taxonomic treatment of the subfamily Celastroideae (Celastraceae) in the state of Espírito Santo, southeastern Brazil, as a part of the ongoing project Flora do Espírito Santo. The work is based on analyses of herbaria specimens and fieldwork since 2012. Two genera and thirteen species are reported for Espírito Santo, covering all the vegetation formations found in the state. Celastrus is represented by one species, C. liebmannii, the unique climbing species of the subfamily in Brazil. Monteverdia are shrubs and trees characterized by fruits 2-valved, pericarp coriaceous and white aril. The genus is represented by twelve species, corresponding nearly to one third of the Brazilian species. Celastrus liebmannii is formally reported by the first time to Espírito Santo. Morphological descriptions, comments, color photographs plates, and identification keys for genera and Monteverdia species are provided.